2018
DOI: 10.1103/physrevlett.120.157701
|View full text |Cite
|
Sign up to set email alerts
|

Nonadiabatic Dynamics in Single-Electron Tunneling Devices with Time-Dependent Density-Functional Theory

Abstract: We simulate the dynamics of a single-electron source, modeled as a quantum dot with on-site Coulomb interaction and tunnel coupling to an adjacent lead in time-dependent density-functional theory. Based on this system, we develop a time-nonlocal exchange-correlation potential by exploiting analogies with quantum-transport theory. The time nonlocality manifests itself in a dynamical potential step. We explicitly link the time evolution of the dynamical step to physical relaxation timescales of the electron dyna… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 49 publications
0
30
1
Order By: Relevance
“…Notably, we found an example of a 'Markov-only' semigroup approximation that is non-perturbative in all parameters, yet simultaneously completely positive (CP) and trace-preserving (TP). It should be noted that this approximation relies only on the exact value of the stationary occupation n(∞) = 144,145 that are based on a mapping to the noninteracting limit studied here.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we found an example of a 'Markov-only' semigroup approximation that is non-perturbative in all parameters, yet simultaneously completely positive (CP) and trace-preserving (TP). It should be noted that this approximation relies only on the exact value of the stationary occupation n(∞) = 144,145 that are based on a mapping to the noninteracting limit studied here.…”
Section: Discussionmentioning
confidence: 99%
“…As a testbed to benchmark the performance of a recently proposed non-adiabatic exchange-correlation potential, 11 we consider a single impurity Anderson model at finite temperature, as depicted in Fig 1(a). The Hamiltonian is given by…”
Section: A Modelmentioning
confidence: 99%
“…8,10 To improve the performance of TDDFT, recently, a non-adiabatic approximation for the Hartree-exchangecorrelation potential of the single-impurity Anderson model was derived by exploiting analogies to quantum transport theory. 11 The derivation is based on a firstorder perturbative treatment in the tunnel coupling between the impurity and the reservoir and uses a Markov approximation for the time propagation in the rate equation approach. It was shown that the resulting nonadiabatic functional improves over its adiabatic counterpart and yields the correct exponential decay of the density after a quench in the gate voltage, see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…but smaller than γ L/R , the interacting spectral function is well approximated by [31,38] In particular for Θ = 0 the Friedel sum rule implies that the zero-bias interacting and KS conductances G αβ = ∂I α /∂V β and G s,αβ = ∂I α /∂V s,β are identical [39]. Since (repeated indices are summed over) (17) the zero-temperature xc voltages must fulfill ∂V µ,xc /∂I ν = 0 at zero currents.…”
Section: I-dft Potentials For the Anderson Modelmentioning
confidence: 99%